Screening of citrus scion-rootstock combinations for tolerance to water salinity during seedling formation (Acta Scientiarum. Agronomy, 2020)
Arid and semiarid regions are vulnerable to water deficits and salinity. Citrus plants are sensitive to saline stress and require the use of tolerant scion-rootstock combinations. Thus, this study aimed to evaluate and classify citrus scion-rootstock combinations with respect to their tolerance to salinity during seedling formation in a protected environment. An experiment was conducted in a randomized block design with a 5 x 12 x 2 factorial scheme corresponding to five levels of water salinity (0.8, 1.6, 2.4, 3.2, and 4.0 dS m-1) applied in 12 citrus rootstocks grafted with two scion varieties: ‘Tahiti’ acid lime and ‘Star Ruby’ grapefruit. The scion-rootstock combinations were evaluated for accumulated dry matter and survival index at 330 days after sowing the rootstocks. Salinity exerted different effects on the dry matter formation of scion-rootstock combinations. ‘Star Ruby’ was less sensitive to salinity, particularly when the rootstocks were the hybrids from ‘Sunki of Florida’ mandarin (TSKFL) with ‘Troyer’ citrange (CTTR) – 013 (TSKFL x CTTR – 013), common ‘Sunki’ mandarin (TSKC) with ‘Argentina’ citrange (CTARG) – 019 (TSKC x CTARG – 019), TSKC with ‘Swingle’ citrumelo (CTSW) – 031 (TSKC x CTSW – 031), and the trifoliate hybrid (HTR) - 069, as well as the varieties Volkamer lemon and Santa Cruz Rangpur lime. When grafted with ‘Tahiti’ acid lime, the rootstocks displaying the less sensitive to salinity were TSKFL x CTTR - 013 and TSKC x CTARG - 019.